Мода для всех. Вязание: [набор открыток] / составитель М. Максимова ; фотографии Д. Власенкова - Максимова М. (Вязание, 1987)
Экземпляры: (20200123) / Инвентарный номер: / Сис.шифр: 37.24 / Авт.знак: В 81 / ББК: 37.248